Comparison of dermatomal sensory block following ultrasound-guided transversus abdominis plane block by the lateral and posterior approaches: A randomized controlled trial - Tomonori Furuya; Jitsu Kato; Yusuke Yamamoto; Noriya Hirose; Takahiro Suzuki (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: Ultrasound (US)-guided transversus abdominis plane (TAP) block is used as a part of a multimodal analgesic regimen in the postoperative period. Lateral approach TAP block (LTAP) has been widely used for postoperative analgesia after lower abdominal surgeries. Posterior approach TAP block (PTAP), which is achieved by more posterior blockade of the anterior ramus of the spinal nerve, also provides profound postoperative analgesia after transverse lower abdominal incision. We investigated the dermatomal sensory block following LTAP and PTAP under US guidance. Material and Methods: Twenty-seven adult female patients undergoing the laparoscopic resection of ovarian tumors under general anesthesia were randomly divided into two groups, those receiving LTAP (Group L, n = 14) and those receiving PTAP (Group P, n = 13). Before induction of general anesthesia, all patients were given bilateral TAP blocks with 15 ml of 0.25% levobupivacaine on each side under US guidance, and the sensory blockade was evaluated. Results: The data are expressed as median (interquartile range [IQR]). PTAP produced a median sensory blockade to sharp touch of three dermatomal segments (IQR 3-4), the most cephalad being T-10 (IQR T-9-T-10), whereas LTAP produced blockade of a median of two segments (IQR 2-2, P = 0.002), the most cephalad being T-10 (IQR T-10-T-10, P = 0.005). Conclusions: PTAP produced a sensory block that involved a greater number of dermatomes and involvement of more cephalad dermatome blocked to sharp touch, compared with LTAP under US guidance.